2019
DOI: 10.22441/jimb.v5i1.5629
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Penerapan Blue Ocean Strategy Pada Pembiayaan Sindikasi Skim Musyarakah Mutanaqishah

Abstract: Penelitian ini bertujuan untuk menganalisis penerapan blue ocean strategy pada pembiayaan sindikasi skim musyarakah mutanaqishah di Bank Syariah X. Adapun identifikasi masalah pada penelitian yaitu ketatnya persaingan di Industri Perbankan dan adanya fluktuasi pertumbuhan pembiayaan. Strategi yang saat ini digunakan mengacu pada konsep marketing mix 7P (product, price, place, promotion, people, process, physical evidence), namun dibutuhkan strategi baru untuk menjauh dari persaingan yang ketat tersebut. Desain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…[14] analyzed the articles on Garuda and concluded that there were 310 articles from 2005 to 2021. The themes of articles include qualitative analysis to other variables [15], single application concept challenge [16], and application of musharakah contract [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…[14] analyzed the articles on Garuda and concluded that there were 310 articles from 2005 to 2021. The themes of articles include qualitative analysis to other variables [15], single application concept challenge [16], and application of musharakah contract [17].…”
Section: Literature Reviewmentioning
confidence: 99%